1999
DOI: 10.1136/jcp.52.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Sulphomucins favour adhesion of Helicobacter pylori to metaplastic gastric mucosa.

Abstract: Aims-To assess the influence of sulphomucin secretion on Helicobacter pylori colonisation and adhesion to metaplastic gastric cells. (J Clin Pathol 1999;52:137-140) Methods-Gastric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…In the evaluation of the infection status, it is worthwhile to note that H. pylori colonization is typically absent in the IM foci of the complete type, whereas it may be present in the adjacent nonmetaplastic gastric mucosa and in IM of the incomplete type (58). In addition, decreased sensitivity of the rapid urease test is observed in subjects taking proton pump inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In the evaluation of the infection status, it is worthwhile to note that H. pylori colonization is typically absent in the IM foci of the complete type, whereas it may be present in the adjacent nonmetaplastic gastric mucosa and in IM of the incomplete type (58). In addition, decreased sensitivity of the rapid urease test is observed in subjects taking proton pump inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Among adults 140 years of age, H. pylori infection may become less prevalent with advanced age [30]. This decrease is thought to directly result from H. pylori-induced damage to gastric epithelium; chronic H. pylori infection leads both to intestinal metaplasia of gastric cells (to which H. pylori adhere less readily) [31,32] and to gastric atrophy and hypochlorhydria (allowing competition from other microorganisms).…”
Section: Epidemiologymentioning
confidence: 99%
“…Interestingly, there appears to be a correlation between the type of glycoconjugate to which microbes preferentially bind and the glycoconjugate-cleavage machinery of the respective microorganisms (Hoyer et al, 1992;Slomiany et al, 1992;Bravo and Correa, 1999;Vimal et al, 2000). Furthermore, it has been suggested that adhesion to mucin can trigger the production of various mucolytic strategies to overcome mucus entrapment.…”
Section: Host-microbe Interactions At Mucosal Interfaces In Metazoansmentioning
confidence: 99%